Intervención farmacéutica en pacientes con diabetes mellitus tipo 2 y neumonía bacteriana en un hospital de Iquitos 2023 - Santana Liao, Aurora Erlita (2024)
Diabetes mellitus type 2 is a chronic metabolic disease defined when blood sugar (or glucose) is high, which over the years leads to serious damage to our entire body and occurs because the body becomes resistant to insulin or does not produce enough insulin. Bacterial pneumonia is an infection that affects the lungs and causes the alveoli to fill with pus produced by Gram positive bacteria. The specific objectives were: Identify sociodemographic characteristics, Identify problems related to medications and Evaluate the impact of hospital pharmaceutical intervention using the Morisky Green test in patients with type 2 Diabetes mellitus and bacterial pneumonia who were treated in the Internal Medicine Hospitalization Service of Hospital III – Iquitos, EsSalud, during the period from December 2023 to June 2024. Quantitative study, prospective, descriptive, observational and cross sectional design. The population was 37 and 39 patients. Methodology used was pharmacotherapeutic monitoring to determine DRPs and the Morisky Green test for treatment adherence. The results obtained in both pathologies, the most frequent in the male sex, ages between 27 to 59 years, 46.2% PRM5 with 84.6% in therapeutic adherence in patients with bacterial pneumonia and in Type 2 Diabetes mellitus from 60 years to plus PRM4 and PRM5 with 40.5%, therapeutic adherence with 81.1%. It is concluded that the impact of the pharmaceutical intervention was favorable in patients with Type 2 Diabetes mellitus and Bacterial pneumonia through the evaluation of the Morisky Green test, carrying out a good pharmacotherapeutic follow-up, which has allowed improving the pharmacotherapeutic treatment, improving the symptoms of both pathologies.